Life Satisfaction in Retirees Who are still Working 1 - Guerson, Luciana Raybolt da S. C.; França, Lucia Helena de F. P.; Amorim, Silvia Miranda (Paidéia (Ribeirão Preto), 2018)
Retirement does not always represent the final exit from the labor market. Work is one of the most important aspects in people’s lives, and a relationship seems to exist between continuity of work during retirement and life satisfaction. This study evaluated the perception of life satisfaction among 230 retirees who were still working. Participants completed a questionnaire containing scales for Life Satisfaction, Job Perception and Reasons for Returning to Work. Correlations and multiple linear regression indicated that perception of the work, satisfaction with income and intrinsic reasons (such as the feeling of productivity) influenced life satisfaction of retirees who returned to work. Our results reinforce the adoption of public and organizational policies to maintain retirees who wish to continue working.